Studying catabolism of protein ADP-Ribosylation - Palazzo, L; James, D; Waddell, I; Ahel, I (Humana Press, 2017)
Protein ADP-ribosylation is a conserved posttranslational modification that regulates many major cellular functions, such as DNA repair, transcription, translation, signal transduction, stress response, cell division, aging, and cell death. Protein ADP-ribosyl transferases catalyze the transfer of an ADP-ribose (ADPr) group from the β-nicotinamide adenine dinucleotide (β-NAD+) cofactor onto a specific target protein with the subsequent release of nicotinamide. ADP-ribosylation leads to changes in protein structure, function, stability, and localization, thus defining the appropriate cellular response. Signaling processes that are mediated by modifications need to be finely tuned and eventually silenced and one of the ways to achieve this is through the action of enzymes that remove (reverse) protein ADP-ribosylation in a timely fashion such as PARG, TARG1, MACROD1, and MACROD2. Here, we describe several basic methods used to study the enzymatic activity of de-ADP-ribosylating enzymes.